TikTok as a Coping Strategy in Learning English during the COVID-19 Pandemic: Exploring the Acceptance and Usage among Malaysian Undergraduates - Ilianis Adnan, Nur; Nur Morat, Berlian; Aboo Bakar, Rofiza; Nozakiah Tazijan, Farina; ., Ikhsanudin; ., Sudarsono (International Journal of English Language Education, 2024)
TikTok has become popular and widely used globally across various fields, including education, particularly during the Covid-19 pandemic, as teaching and learning methods shifted to online distance learning from physical interaction. This paper explores TikTok as a coping strategy in learning English during the Covid-19 pandemic as well as the acceptance and usage of TikTok among Malaysian undergraduates. This quantitative study employed a questionnaire-based approach to gather insights from 130 undergraduate students at a local university in Penang and the study delves into the frequency and extent of TikTok engagement, revealing that a majority of the 130 surveyed students actively utilise the platform multiple times a day. The collected data were then subjected to thorough analysis to identify patterns, trends, and key factors influencing the participants’ attitudes and behaviours towards TikTok in the context of language learning. The results underscore TikTok’s emergence as a noteworthy and frequently employed tool in the educational landscape, aligning with existing literature that recognises digital platforms as valuable supplementary tools in education.